2011
DOI: 10.1186/bcr2893
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase expression and telomere length in breast cancer and their associations with adjuvant treatment and disease outcome

Abstract: IntroductionTelomere length plays important roles in maintaining genome stability and regulating cell replication and death. Telomerase has functions not only to extend telomere length but also to repair DNA damage. Studies have shown that telomerase may increase cancer cell resistance to DNA-damaging anticancer agents; tamoxifen may suppress telomerase expression in breast cancer cells. This study aimed to investigate the role of telomere length and telomerase activity in breast cancer prognosis.MethodsqPCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…The detection of increased telomerase activity and shortening of telomeres are hypothesized to serve as specific signals of carcinogenesis. According to a number of studies (25)(26)(27), the detection of telomerase activity or telomere length alterations may be observed either in migrating cancer cells or in peripheral blood leukocytes. Such results may provide an opportunity to distinguish or qualify patients with differential cancer stages or grades.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of increased telomerase activity and shortening of telomeres are hypothesized to serve as specific signals of carcinogenesis. According to a number of studies (25)(26)(27), the detection of telomerase activity or telomere length alterations may be observed either in migrating cancer cells or in peripheral blood leukocytes. Such results may provide an opportunity to distinguish or qualify patients with differential cancer stages or grades.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to explore molecular biomarkers to guide clinical decision-making with regard to the treatment of GC. TA is thought to be a critical step in the evolution of most tumor types (34)(35)(36)(37), including GC (38,39). Considerable clinical research has been conducted with the aim of assessing the correlation between TA expression and clinicopathological outcome in patients with GC, but the Size Histo T N M TNM >5 cm P/U T3/T4 positive/ positive/ TIII/IV (<5 cm) (W/M) (T1/T2) (negative) (negative) (TI/TII) Liu et al (27) 2008 English China 26 (14) --20 (6) 22 (4) 11 (15) 24 (2) Yang et al (15) 2001 English China 40 (2) 26 (14) 30 (10) 26 (14) 20 (20) -17 (23) Wu et al (17) 2006 English China 52 (12) 23 (29) 49 (3) 40 (12) 37 (15) 14 (38) 33 (19) Hu et al (23) 2004 English China 18 (17) 10 (8) 14 (4) 7 (11) 14 (4) 10 (8) -Zhan et al (31) 1999 English China 81 (13) 46 (35) 43 (38) 68 (13) 51 (30) -60 (21) Hu et al (16) 2009 English China 41 (5) 28 (13) 33 (8) 21 (20) 5 (36) 30 (11) -Wang et al (18) 2004 English China 32 (9) 19 (13) 25 (7) (21) 43 (1) 18 …”
Section: Discussionmentioning
confidence: 99%
“…disease or survival outcomes, 13 whereas other studies have shown that TL was related to breast cancer risk 46,51 and survival. 10,46,47 Although interpretation remains difficult, the results of the current study nonetheless provide provocative new data that suggest it is possible to influence TL in cancer survivors through the use of psychosocial interventions involving group support, emotional expression, stress reduction, and mindfulness meditation.…”
mentioning
confidence: 95%
“…[10][11][12] However, the relationships between TL and the clinical or pathological features of tumors are still not clearly understood. 13 Recent emerging research has suggested that TL and its enzyme telomerase may be susceptible to psychosocial influences, particularly stress. 14 Telomerase is the specialized cellular reverse transcriptase that elongates telomeric DNA, thereby counteracting the telomere shortening that occurs with successive rounds of cell division.…”
Section: Introductionmentioning
confidence: 99%